Constraining the age of the last geomagnetic reversal from geochemical and magnetic analyses of Atlantic, Indian, and Pacific Ocean sediments - Valet, Jean-pierre; Bassinot, Franck; Simon, Quentin; Savranskaia, Tatiana; Thouveny, Nicolas; Bourlés, Didier L.; Villedieu, Anouk (Earth and Planetary Science Letters, 2019)
We studied four marine sediment records of the Matuyama–Brunhes geomagnetic reversal from four sites located in the Indian, Atlantic and western Pacific oceans. The results combine paleomagnetic, cosmogenic nuclide beryllium (10Be) and oxygen isotope analyses that were performed on the same samples in order to avoid any stratigraphic bias. The three records from the equatorial Indian Ocean and North Atlantic Ocean did not reveal any offset between the authigenic 10Be/9Be ratio (Be-ratio) peak and the interval of low relative paleointensity (RPI) that characterizes the reversal. The lower and upper limits of transitional directions are also concomitant with the increased atmospheric 10Be production that accompanied the geomagnetic dipole intensity decrease. In contrast, the record from western equatorial Pacific Ocean sediments was found 18 cm below the Be-ratio changes as a result of late magnetization acquisition. At all four sites, maximum 10Be production occurred at the same period soon after the maximum of Marine Isotope Stage 19 (MIS 19) and, therefore, indicates its synchronous worldwide character. Such features are effectively observed from the Be-ratio signals and their relationship with the magnetic transition interval, which further confirms the synchronous character of the transition. Taking all dating uncertainties (1.6 ka between sites and 5 ka for the age model) into consideration, our records suggest a mean reversal age of 772.4 ± 6.6 ka. The age of the transition in the Atlantic Ocean record is closer to 774 ka but this difference is within the limit of significance.